2021
DOI: 10.1038/s41467-021-22403-w
|View full text |Cite
|
Sign up to set email alerts
|

Graphene collage on Ni-rich layered oxide cathodes for advanced lithium-ion batteries

Abstract: The energy storage performance of lithium-ion batteries (LIBs) depends on the electrode capacity and electrode/cell design parameters, which have previously been addressed separately, leading to a failure in practical implementation. Here, we show how conformal graphene (Gr) coating on Ni-rich oxides enables the fabrication of highly packed cathodes containing a high content of active material (~99 wt%) without conventional conducting agents. With 99 wt% LiNi0.8Co0.15Al0.05O2 (NCA) and electrode density of ~4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…We prepared Gr dispersions by an electrochemical exfoliation method with commercially available graphite foils [ 15 , 16 , 17 ]. By applying a DC voltage (+10 V), a graphite foil was exfoliated into Gr sheets in an aqueous ammonium persulfate solution (0.5 M), due to the evolution of gases, such as SO 2 and O 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We prepared Gr dispersions by an electrochemical exfoliation method with commercially available graphite foils [ 15 , 16 , 17 ]. By applying a DC voltage (+10 V), a graphite foil was exfoliated into Gr sheets in an aqueous ammonium persulfate solution (0.5 M), due to the evolution of gases, such as SO 2 and O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The exfoliated Gr sheets have lateral sizes of 0.1–2 μm and an average thickness of 4.6 nm (refer to Figure S1 ). The Gr surface/edges appeared to be partially oxygen-functionalized (C–OH/C–O/C=O) due to the oxidation of graphite by OH – ions during the electrochemical process on the basis of XPS C 1s spectra ( Figure S2 ) [ 16 , 17 ]. We performed confocal Raman mapping on the exfoliated Gr sheets, which showed the high-intensity G peak and 2D peak at ~1580 and ~2700 cm −1 , respectively, with an intensity ratio of D to G (I D /I G ) of ~0.3 ( Figure S3 ), which is much lower than that of chemically or thermally reduced graphene oxides (I D /I G = 1.2–1.5) [ 15 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared to pristine NMC811, the graphene composite exhibited higher capacity at 5 C (127 vs. 160 mA h g −1 , respectively) and a better cycle life. Park et al produced a conformal graphene coating on NCA and NMC811 particles by employing an amphiphilic surfactant, 1,2-distearoylsn-glycero-3-phosphoethanolamine-N-[methoxy(polyethyleneglycol) (DSPE-mPEG), which acts as a glue to bind the hydrophobic basal plane of graphene to the hydrophilic lithium hydroxide or lithium carbonate on the surface of NCA or NMC811 particles, as shown in Figure 11 [135]. Their results showed that the conformal graphene coating could eliminate the necessity of adding carbon blacks as conductive additives and thus a high active material content (99 wt.%) and, as a result, a high electrode density (~4.3 g cm −3 vs.~3.3 g cm −3 for 96 wt.% NCA electrode with the carbon black) were achieved.…”
Section: Graphene-enhanced Cathode Materials 41 Graphene-enhanced Cathode Materials For Lithium-ion Batteriesmentioning
confidence: 99%
“…The rate capability testing results of the two samples demonstrated opposite effects when compared to the pristine NCA: the sample coated with graphene nanodots showed improvement in capacity at all tested C-rates, while the rGO-coated sample displayed a lower capacity than that of the pristine sample at all tested C-rates. We summarize the results from two studies [135,136] that both used 0.5 wt.% graphene (or rGO) coating on NCA particles and present a visual comparison in Figure 12. The Y-axis represents the percentage of capacity changes defined as [(specific capacity of the coated sample)-(specific capacity of the non-coated sample)] divided by (specific capacity of the non-coated sample) at 0.1 C. The SEM micrographs clearly showed a more compact coating when the larger graphene (rGO) was used as the coating material.…”
Section: Graphene-enhanced Cathode Materials 41 Graphene-enhanced Cathode Materials For Lithium-ion Batteriesmentioning
confidence: 99%
“…Graphene is a two-dimensional, one-atom-thick layer of carbon, in which atoms are oriented in a hexagonal crystal lattice. The promising and appealing properties of graphene-based materials are widely used in many research-oriented fields, like fuel cells [ 1 , 2 ], batteries [ 3 , 4 ], screens [ 5 , 6 ], sensors [ 7 , 8 ], flexible electronics [ 9 , 10 ], tissue engineering [ 11 , 12 ], and membranes [ 13 , 14 ]. Moreover, their unique features result in an increase of materials’ mechanical strength, electrical and thermal conductivity, and surface area and flexibility [ 15 , 16 , 17 ], making them the most preferred choice in experimental procedures.…”
Section: Introductionmentioning
confidence: 99%